Prospects for the development of the vfsk GTO, taking into account the monitoring data of test results - E.N. Bobkova; L.V. Vinogradova; E.A. Zyurin; E.N. Petruk (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the prospects for the development of the VFSK GTO, taking into account the results of monitoring the implementation of the complex in 2018-2021 on the territory of the Russian Federation. Methods and structure of the study. In the course of scientific work, sources containing information on organizational and managerial, personnel, material and technical activities, physical activity of the population of the Russian Federation were studied during the implementation of the GTO complex, including the number of those who blunted and completed the tests of the complex, the level of physical fitness of the population of the Russian Federation on based on testing physical qualities and applied skills in the population from 6 to 70 years and older. Results and conclusions. It has been established that the results of monitoring the implementation of the GTO complex for 2018-2021 show a positive trend in the number of people who started (24.2%) and completed the tests (34.9%), with the exception of 2020, in which there is a decline in all indicators. A two-fold increase in the number of those who completed the tests for insignia in 2021 was revealed, an increase in the number of children aged 6-12 years who completed the tests of the complex was recorded up to 15%, with a clear predominance of adolescents aged 16-17 years (34%) and a steady decrease in the number of adults as aging (up to 3.4% in stage XI). Analysis of the results of organizational and managerial activities for the preparation and evaluation of compliance with the test standards of the complex in the constituent entities of the Russian Federation testifies to the formed model of organizational activity and ensuring the process of implementing the GTO complex by testing centers. The presented proposals for improving the GTO complex are aimed at optimizing state requirements related to the progressive development of standards in accordance with the current level of physical fitness of the population from 6 to 70 years and older and the industry development targets.